Elements that impose limits on international ethics - Paul Popa (CES Working Papers, 2019)
In order to function, the ethical norm creates a system, called and known as an ethical system. It is separated from the legal system, as the ethical norm is separated from other types of norms or law. The comparative model allows us to see to what extent there are common elements of construction and operation of these systems to see if they are the ones that impose or limit the international ethics. Only after reviewing the characteristics of international ethics we will able to evaluate these limits through several dimensions in which ethics is encountered or invoked (human rights, humanitarian interventions, non-proliferation etc.).
Keywords: 330; ethics; international law; ethical system; limits